Dinámica de crecimiento de especies forestales de una parcela permanente en bosque seco de la parroquia Mangahurco, cantón Zapotillo, provincia de Loja - López Beltran, Jonathan Michael (2023)
The dynamics of species and forest growth allows us to know the changes in the composition and structure of a forest over a period of time. The research was developed in the dry forest of El Tabanco sector, Mangahurco parish, Zapotillo canton; with the objective of determining the dynamics and evaluating the growth of forest species in seven years. A permanent plot of 1 ha established in 2015 was remeasured, the diameter (D1,30 m) and total height of all individuals with D1.30 m ≥ 5 cm were measured; in addition, deaths and recruitments were recorded. The average growth and annual periodic growth of diameter, height, basal area and volume were calculated. It was recorded 1 048 individuals/ha, corresponding to 33 species of 32 genera and 18 botanical families, the mortality rate is 2,33 % corresponding to 162 individuals/ha and 1,42 % recruitment rate of 99 individuals/ha, with a dynamism of 1,87 %. In seven years the average growth in diameter was 0,0118 m/ha; height 0,9095 m/ha; basal area 0,0045 m2/ha and volume 0,0331 m3/ha. The annual periodic increment (IPA) in diameter 0,0017 m/ha/year; height 0,1299 m/ha/year; basal area 0,0006 m2/ha/year and volume 0,0047 m3/ha/year. The species with the highest average growth in diameter is Erythrina velutina with 0,0483 m/ha; height Machaerium millei 1,6178 m/ha; basal area 0,0510 m2/ha and volume Ceiba trischistandra with 0,4864 m3/ha. In seven years the species of the plot had an increase in basal area of 2,43 m2/ha and a volume of 20,93 m3/ha, constituting a dynamic growth, which allows the forest to remain in balance. Key words: Average growth, Periodic annual increment, mortality, recruitment.